Trimethoxysilyl end-capped hyperbranched polyglycidol/polycaprolactone copolymers for cell delivery and tissue repair: synthesis, characterisation and aqueous solution properties. (March 2019) - González-Chomón, Clara; Garamus, Vasil M.; Rangelov, Stanislav; Ebdon, John R.; Novakov, Christo; Halacheva, Silvia S.
Graphical abstract: Highlights: New PCL-HBPG/SiHBPG triblock copolymers were developed. They will be utilised for the preparation of covalently linked injectable gels. The copolymers formed stable multicore particles in aqueous solutions. The polymers' structure, composition and solution properties were correlated. Abstract: New PCL-HBPG/SiHBPG triblock copolymers composed of a polycaprolactone (PCL) core with two outer blocks of trimethoxysilyl end-capped hyperbranched polyglycidol (HBPG/SiHBPG), of varying molecular weight, have been successfully synthesised and characterised. The effect of copolymer composition and structure upon the crystallization, melting, thermal degradation and aqueous solution behaviour were investigated at various temperatures. In aqueous solution, at concentrations above their corresponding critical aggregation concentration the PCL-HBPG/SiHBPG copolymers readily self-assemble into large multicore structures composed of PCL domains and corona consisting of HBPG/SiHBPG branches. The multicore structures were stabilized by numerous hydrogen-bonds from the HBPG moieties as well as via formation of siloxane crosslinks (i.e. SiOSi bonds). As the formation of the siloxane linkages is irreversible the PCL-HBPG/SiHBPG-based particles will be covalently crosslinked at higher concentrations in vivo and form injectable gels scaffolds that will be biocompatible and capable of invoking cell attachment and differentiation without the need for exogenous biological stimuli.